2010
DOI: 10.1259/bjr/25788274
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of axillary lymph nodes with high tangential fields in breast radiotherapy

Abstract: ABSTRACT. The aim of this study is to evaluate the coverage of axillary nodal volumes with high tangent fields (HTF) in breast radiotherapy and to determine the utility of customised blocking. The treatment plans of 30 consecutive patients with early breast cancer were evaluated. The prescription dose was 50 Gy to the whole breast. Axillary level I-II lymph node volumes were delineated and the cranial border of the tangential fields was set just below the humeral head to create HTF. Dose-volume histograms (DVH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…However, dosedistribution analysis indicated that the entire volume of the axilla is not irradiated with the entire prescribed dose. It is now estimated that, using standard tangential fields, more than 50% of level I and 20-30% of level II nodes receive 95% of the prescribed radiation dose [8,9,11,12]. The advantage of the field-in-field plan over the conventional wedge-inserted plan was also demonstrated in other reports [7,13].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, dosedistribution analysis indicated that the entire volume of the axilla is not irradiated with the entire prescribed dose. It is now estimated that, using standard tangential fields, more than 50% of level I and 20-30% of level II nodes receive 95% of the prescribed radiation dose [8,9,11,12]. The advantage of the field-in-field plan over the conventional wedge-inserted plan was also demonstrated in other reports [7,13].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, the strength of this study is that it shows the clinical use of 3-D treatment planning to irradiate intentionally the large volume of level I and II nodes. While retrospective dosimetric studies have suggested the technical use of high tangent fields [7,11,12,13], this is the first study to demonstrate the impact of improved dose distribution on regional control in breast cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…That can have direct correlation, with standard tangents, the axilla receives a significant incidental dose but still adequate for clinical control of disease is unknown [18,19]. Substantial variability was observed in contouring the targets and organ at risk between observers and the structure overlaps were as low as 10% and volume variation had standard variation up to 60% [20].…”
Section: Discussionmentioning
confidence: 99%
“…This approach was based on several studies investigating the dose delivered to the ALNs by conventional tangential fields, and the exploration of techniques yielding an improved coverage of level I by minor field extensions in cranial direction [29,30,31]. This technique is also recommended in the new textbook on Radiation Oncology edited by Perez and Brady [18].…”
Section: Positive Sn/no Alnd - Implications For Rtmentioning
confidence: 99%